Development and validation of a fluorimetric method to determine curcumin in lipid and polymeric nanocapsule suspensions - Letícia Mazzarino; Ismael Casagrande Bellettini; Edson Minatti; Elenara Lemos-Senna (Universidade de São Paulo, 2010)
A simple, rapid, and sensitive fluorimetric method was developed and validated to quantify curcumin in lipid and polymeric nanocapsule suspensions, using acetonitrile as a solvent. The excitation and emission wavelengths were set at 397 nm and 508 nm, respectively. The calibration graph was linear from 0.1 to 0.6 µg/mL with a correlation coefficient of 0.9982. The detection and quantitation limits were 0.03 and 0.10 µg/mL, respectively. The validation results confirmed that the developed method is specific, linear, accurate, and precise for its intended use. The current method was successfully applied to the evaluation of curcumin content in lipid and polymeric nanocapsule suspensions during the early stage of formulation development. Um método fluorimétrico simples, rápido e sensível foi desenvolvido e validado para quantificação da curcumina em suspensões de nanocápsulas lipídicas e poliméricas, usando acetonitrila como solvente. Os comprimentos de onda de excitação e emissão foram 397 nm e 508 nm, respectivamente. Nas condições testadas, a curva de calibração demonstrou-se linear na faixa de 0,1 a 0,6 µg/mL, exibindo coeficiente de correlação de 0,9982. Os limites de detecção e quantificação foram 0,03 e 0,10 µg/mL, respectivamente. Os resultados da validação confirmaram que o método desenvolvido é específico, linear, exato e preciso para o uso proposto. O presente método foi aplicado com sucesso para a avaliação do teor de curcumina nas suspensões de nanocápsulas lipídicas e poliméricas durante o estágio inicial do desenvolvimento da formulação.